Development and modernization of OIC member countries: A study based on selected indicators - Md. Noon, Hazizan; Karim, AHM Zehadul; Uddin, Md. Sayed (IIUM Press, 2018)
This paper attempts to analyze the performance of 57 member states of the Organization of Islamic Cooperation (OIC)based on selected indicators of some sectors namely demography, economics, education and technology and innovation. Specifically, it aims at firstly portraying an overview of OIC performance based on six selected indicators followed by analyzing the relationship between selected development variables with literacy and exploring the state of OIC performance as indicated by their achievement based on selected indicators. The study was undertaken vis-à-vis the prevailing theories on modernization and development as well as the widely asserted underdevelopment of the contemporary Muslim ummah as claimed by numerous contemporary Muslim scholars. The data were solicited among others from the World Bank Database, Statistical, Economic, and Social Research and Training, Centre of Islamic Countries (SESRIC) of OIC and some previous studies. They were then analyzed using SPSS with the results being generated mainly through the use of descriptive statistics. Among others, study found that there is a positive correlation between Muslim countries’ urban population growth and literacy rate, there is a steady decline in the number of OIC countries as they are categorized from lower to higher income category placement and the percentage of the scientific publications of all 57 OIC countries is far below that of any one single developed nation.